Implementasi Putusan Mahkamah Konstitusi Tentang Kedudukan Anak Luar Kawin Di Wilayah Pengadilan Agama Kelas 1A Bengkulu Dan Dinas Kependudukan Dan Catatan Sipil Kota Bengkulu - Dimas Dwi Arso; Edytiawarman Edytiawarman; Slamet Muljono; Nurhani Fithriah (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2022)
The decision of the Constitutional Court Number 46/PUU-VIII/2010 regarding the legal status of children out of wedlock, decided that: Children born out of wedlock only have a civil relationship with their mother and their mother's family as well as with a man as their father which can be proven based on science. and technology and/or other evidence according to the law having a civil relationship, including a civil relationship with his father's family, has raised pros and cons not only among the public, but also among law enforcement and the Indonesian Ulema Council. This study aims to determine and analyze (1) the implementation of the Constitutional Court Decision No. 46/PUU-VIII/2010 concerning the Position of Out-of-Marriage Children in the Class 1A Bengkulu Religious Court Area and the Bengkulu City Population and Civil Registry Office, (2) legal consequences of Constitutional Court Decision No. 46/PUU-VIII/2010 concerning the position of children out of wedlock to the rights of children out of wedlock, and the opinion of the Judge of the Bengkulu Class 1A Religion Court. 46/PUU-VIII/2010 concerning the position of children out of wedlock. The research method was carried out empirically and normatively. The data used are primary data and secondary data. Primary data was obtained by means of direct interviews with parties related to handling the problem of the object of research, while secondary data was obtained by means of library research. The results of the research are expected to serve as input for decision makers and society in general. Field results show that until now there has never been an application for determination of the position of a child out of wedlock in the area of the Religious Court Class 1A Bengkulu, and if there is an application for the determination of a child out of wedlock, an examination and proof will be carried out regarding the origin of the child, while for the Department of Population and Records The Bengkulu City Civil Service is only for disfiguring and administering the child status determination which has been determined by the Bengkulu Class 1A Religious Court. The legal consequences of Constitutional Court Decision No. 46/PUU-VIII/2010 concerning the position of illegitimate children with respect to the rights of children born out of wedlock only have a civil relationship with their mother and biological father and the families of their father and mother, but only have a kinship relationship with their mother and with their mother's family, while to his biological father and his father's family, the child is not related by lineage. The opinion of the Indonesian Ulema Council of Bengkulu City is in line with the opinion of the Indonesian Ulema Council which issued a fatwa that the Constitutional Court Decision No. 46/PUU-VIII/2010 Regarding the Position of Children Out of wedlock to the rights of children out of wedlock that children resulting from adultery do not have nasab, marriage guardian, inheritance, and nafaqah relationships with men resulting in their birth. Children resulting from adultery only have kinship, inheritance, and nafaqah relationships with their mothers and their mother's family